Effect of Lemuru Fish–Based Local Snacks on HAZ and DHA Levels among Stunted Toddlers: A Quasi-Experimental Study - Estuasih Dyah Pertiwi; Sunarto Sunarto; Mohamad Reza Assidhiq; Arwin Muhlihsoh; Arvina Dian Wahyu Permatasari (Journal of Health and Nutrition Research, 2026)
Stunting among toddlers remains a persistent public health problem in low- and middle-income countries and is strongly associated with chronic undernutrition, including inadequate intake of omega-3 long-chain polyunsaturated fatty acids such as docosahexaenoic acid (DHA), which are essential for optimal growth and development. Lemuru fish (Sardinella lemuru), a locally abundant and affordable source rich in DHA, has considerable potential as the basis for food based snacks in sustainable nutrition interventions. In this study, stunted toddlers in the intervention group received the lemuru fish–based snack daily for 12 weeks (each serving provided 31.35 mg DHA); DHA distribution was performed once weekly. This study aimed to evaluate the effect of lemuru fish–based local snacks on Height-for-Age Z-score (HAZ) and DHA levels among stunted toddlers. A quasi-experimental study with a pretest–posttest control group design was conducted involving 28 stunted toddlers, equally divided into an intervention group (n = 14) and a control group (n = 14). The intervention group received lemuru fish–based snacks during the intervention period, while the control group received no supplementation. Measurements of HAZ and DHA levels were obtained before and after the intervention. Bivariate analyses indicated greater improvements in HAZ and DHA levels in the intervention group compared with the control group. After adjustment for child and household characteristics using a general linear model (ANCOVA), the intervention was associated with significant improvements in HAZ (B = 0.247; p = 0.038) and DHA levels (B = 7.554 mg/dL; p = 0.017). These findings indicate that lemuru fish–based local snacks effectively improve linear growth and DHA status and represent a promising, locally sourced strategy for stunting prevention and management.